Aculeaquamide A, cytotoxic paraherquamide from the marine fungus Aspergillus aculeatinus WHUF0198. Issue 17 (1st September 2022) - Wu, Jun; Wang, Fuqian; He, Li-Ming; Zhou, Si-Yuan; Wang, Shou-Bao; Jia, Jia; Hong, Kui; Cai, You-Sheng
Abstract: A new paraherquamide named aculeaquamide A (1 ) was isolated from an EtOAc extract of Aspergillus aculeatinus WHF0198 culture media together with five known compounds. The structures of the isolated compounds were elucidated by analysis of NMR and MS data, and the absolute configurations of compound 1 was confirmed by CD spectroscopic methods. All isolated compounds were evaluated for their cytotoxicity against three human cancer cell lines, Bel-7402, A549, and HCT-116. Compounds 1 and 2 showed cytotoxicity against Bel-7402 with IC50 values of 3.3 and 1.9 μ M, respectively. Graphical Abstract: UF0001